2011
DOI: 10.1007/s13361-011-0248-z
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Between Peptide O-Sulfo- and O-Phosphotyrosine Residues by Negative Ion Mode Electrospray Tandem Mass Spectrometry

Abstract: Unambiguous differentiation between isobaric sulfated and phosphorylated tyrosine residues (sTyr and pTyr) of proteins by mass spectrometry is challenging, even using high resolution mass spectrometers. Here we show that upon negative ion mode collision-induced dissociation (CID), pTyr- and sTyr-containing peptides exhibit entirely different modification-specific fragmentation patterns leading to a rapid discrimination between the isobaric covalent modifications using the tandem mass spectral data. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Differentiating sulfotyrosine from phosphotyrosine is challenging based on the nearly isobaric nature of the modifications, with sulfation adding 79.956 Da and phosphorylation adding 79.966 Da. Other studies have approached the problem by exploiting differences in the neutral loss characteristics of phosphotyrosine- and sulfotyrosine-containing peptide anions upon CID [30]. Based on the UVPD fragmentation behavior of four deprotonated phosphotyrosine-containing peptides including TSTEPQpYQPGENL, Ac-DpYVPML-NH 2 , RRLIEDAEpYAARG, and Ac-IpYGEF-NH 2 , it appears that a similar method monitoring sulfo and phospho neutral losses can be used for UVPD.…”
Section: Resultsmentioning
confidence: 99%
“…Differentiating sulfotyrosine from phosphotyrosine is challenging based on the nearly isobaric nature of the modifications, with sulfation adding 79.956 Da and phosphorylation adding 79.966 Da. Other studies have approached the problem by exploiting differences in the neutral loss characteristics of phosphotyrosine- and sulfotyrosine-containing peptide anions upon CID [30]. Based on the UVPD fragmentation behavior of four deprotonated phosphotyrosine-containing peptides including TSTEPQpYQPGENL, Ac-DpYVPML-NH 2 , RRLIEDAEpYAARG, and Ac-IpYGEF-NH 2 , it appears that a similar method monitoring sulfo and phospho neutral losses can be used for UVPD.…”
Section: Resultsmentioning
confidence: 99%
“…In the past few decades, continuous efforts have been devoted to the investigation of the dissociation reactions of charged compounds derived from protonation [4][5][6][7][8] or deprotonation [9][10][11][12][13]. On the other hand, the mass spectrometric fragmentations of metal cationized, especially lithiated biomolecules, have attracted much attention because of the desire to measure intrinsic metal ion affinity and identify the binding sites [14,15], and because the interesting dissociation pathways exhibited by these compounds are usually different from the protonated and deprotonated analogues [16,17].…”
mentioning
confidence: 99%
“…4B, inset). Other analytical workflows, including higher resolution positive ion mode or negative ion mode ESI-MS/MS analyses would be required to distinguish between sulfation or phosphorylation at Y 45 [83][84][85] Analysis of the MS1 spectra of F 41 WKQY 45 VDGDQCE 54 peptides showed that Y 45 is largely unmodified in rFIX from both H1 and H2 bioreactors ( Supplementary Fig. S6B).…”
Section: Characterization Of Known and New Ptms On Purified Rfixmentioning
confidence: 99%